Proposal for a predictive scale of cognitive impairment in adult patients with neurocysticercosis - Jorge Luis Anaya González; Francisco López-Muñoz; Erlen Carmona Alvarez-Builla; Adriana Edit Miniet Castillo; Laudelina Moreira Tusell (Medisur)
Background: cognitive impairment in patients with neurocysticercosis is frequent, therefore, it is very useful to have prognostic instruments to establish a better management of it. Objective: to propose a predictive scale of cognitive impairment in adult patients with neurocysticercosis. Methods: study with a correlational, prospective and cross-sectional design, which included 93 patients with neurocysticercosis. Through data provided by previous research, the variables related to the appearance of cognitive impairment were selected in the bivariate analysis (p<0.05). As a multivariate analysis technique, a multidimensional scaling (PROXSCAL) was performed (s-stress < 0.001 and Tucker's congruence coefficient > 0.999). The prognostic performance of each of the variables was determined by means of sensitivity, specificity, and positive and negative predictive values, with their respective 9 5% confidence intervals. Results: a scale with a dichotomous format was developed, which included 7 factors (4 clinical and 3 tomographic), with which a score of 0 to 7 points was obtained for the prediction of cognitive impairment in adult patients with neurocysticercosis, with a probability of: 0-1 point: 75.3 %; 2-3 points: 95 %; ≥ 4 points: 96 %. Conclusion: the proposed instrument has an acceptable prognostic accuracy; it is simple, reproducible and requires little time for its application. This score can improve the quality of care for patients with neurocysticercosis, since it allows guiding the management of this condition